S69 Verification of genetic associations with scleroderma associated interstitial lung disease. (12th November 2019) - Stock, CJW; DeLauretis, A; Visca, D; Daccord, C; Kokosi, M; Kouranos, V; Margaritopoulos, G; George, PM; Molyneaux, PL; Chua, F; Maher, TM; Abraham, DJ; et al.
Abstract : Although genetic associations with scleroderma (SSc) as a whole are clearly established, very little is known on genetic susceptibility to SSc-associated interstitial lung disease (SSc-ILD) specifically. A number of common gene variants have been associated with SSc-ILD, but most have not been replicated in separate populations. We genotyped 4 SNPs in IRF5, and one in each of STAT4, CD226, and IRAK1, in 633 Caucasian patients with SSc, of whom 379 had ILD. The control population (n=503) comprised individuals of European descent from the 1000 Genomes project. Statistical analysis was performed using Unphased v 3.1 and STATA12. Three of the IRF5 SNPs and the STAT4 rs7574865 were significantly associated with SSc compared to controls: rs2004640 (p=0.0013), rs4728142 (p=0.019), rs10488631 (p=0.0025) and STAT4 rs7574865 (p=0.00013). Two SNPs in IRF5 showed a significant difference between patients with SSc-ILD and controls; rs2004640 (p=0.01), and rs10488631 (p=0.028). Three SNPs in IRF5 showed a significant difference between controls and patients without ILD, rs4728142 (p=0.036), rs10488631 (p=0.0023), and rs2004640 (p=0.0042), as did STAT4 rs7574865 (p=4.2×10 -7 ). A significant difference between SSc with and without ILD was only observed for STAT4 rs7574865, which was less frequent in patients with ILD (MAF 0.27 compared to 0.36, p=0.00093). An association between time to decline in FVC by ≥10% was seen for IRF5 rs10488631 (p=0.007), and for CD226 rs763361 (p=0.029). In conclusion, of the seven tested SNPs, STAT4 rs7574865 was protective against ILD. IRF5 and CD226 variants may be associated with progressive SSc-ILD and will need to be further tested.